Police Education in the USA. (21st August 2018) - Cordner, Gary
Abstract: Higher education for police has a 100-year history in the USA. Initially, it incorporated both 'education' and much of what is now considered 'training', out of necessity because police occupational training had yet to be widely implemented. Since the 1960s, though, separate police training institutions and systems have been established throughout the country. In conjunction with this bifurcation of education and training, the dominant higher education model for police became 'criminal justice'. Over the last 40 years, criminal justice has become a very popular field of study in American colleges and universities, curricula have broadened to include a wide variety of crime and justice topics, and faculty academic credentials have risen to meet and exceed higher education standards. In the process, however, policing has become a smaller and smaller part of the criminal justice educational enterprise. Today, what passes for police education in the USA has very little police in it.